1993
DOI: 10.1159/000187285
|View full text |Cite
|
Sign up to set email alerts
|

Bacteremia in Patients on Chronic Hemodialysis

Abstract: A prospective epidemiologic survey of bacterial infections in chronic hemodialysis patients was conducted from September 1, 1989 to February 28,1990 in 27 dialysis units. Of the 1,455 patients enrolled in the study, 55 presented 63 episodes of bacteremia (incidence of 0.7 bacteremia per 100 patient-months). The portal of entry of sepsis was the vascular access in 50.8% of the episodes. The causative microorganisms were most often gram-positive cocci (69.8%). 23% of the teremic patients had a serum ferritin > 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
124
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(129 citation statements)
references
References 11 publications
2
124
0
3
Order By: Relevance
“…The mortality rate was 30.89%, 24.59%, and 42.02% for all patients, HD patients, and PD patients, respectively, similar to previous reports of other populations (12,(18)(19)(20). For HD patients, previous reports demonstrated that S. aureus, coagulase-negative Staphylococcus, and Gram-negative rods were the major causative microorganisms of bacteremia, and vascular access was the major primary source of bacteremia (12,(18)(19)(20). The mortality rate of bacteremia ranged from 6.3% to 33% in HD patients (18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The mortality rate was 30.89%, 24.59%, and 42.02% for all patients, HD patients, and PD patients, respectively, similar to previous reports of other populations (12,(18)(19)(20). For HD patients, previous reports demonstrated that S. aureus, coagulase-negative Staphylococcus, and Gram-negative rods were the major causative microorganisms of bacteremia, and vascular access was the major primary source of bacteremia (12,(18)(19)(20). The mortality rate of bacteremia ranged from 6.3% to 33% in HD patients (18)(19)(20).…”
Section: Discussionsupporting
confidence: 89%
“…S. aureus was the most common microorganism in all patients (23.53%) and in HD patients (27.53%), whereas Coagulasenegative Staphylococcus (21.27%) was most common microorganism in PD patients. The mortality rate was 30.89%, 24.59%, and 42.02% for all patients, HD patients, and PD patients, respectively, similar to previous reports of other populations (12,(18)(19)(20). For HD patients, previous reports demonstrated that S. aureus, coagulase-negative Staphylococcus, and Gram-negative rods were the major causative microorganisms of bacteremia, and vascular access was the major primary source of bacteremia (12,(18)(19)(20).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Several groups of patients have a well-defined risk for serious infections due to S. aureus; patients undergoing major surgery (including cardiothoracic and orthopedic surgery, among others) and patients undergoing chronic hemodialysis are among those populations at the highest risk. 22 Availability of a S. aureus vaccine for at-risk patients would represent a new paradigm in addressing this medical need, particularly in light of increasing antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, enhanced protection from lethal sepsis in rodent models was mediated by both IsdB-specific CD4+ T cells, 16 and IsdB-specific mAb. 10,13,[17][18][19] The protection afforded by vaccination with IsdB in rodents was lost if the animals were challenged with an IsdB fluid (9), surgical tissue (22), synovial fluid (17), sputum (9), or other sites (5) during routine clinical care. Of the 52 S. aureus isolates, 51 were spa typed; a single isolate failed to grow sufficiently in culture for spa determination.…”
Section: Introductionmentioning
confidence: 99%